2014
DOI: 10.1007/s11655-014-1742-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hydro-alcoholic extract of Nigella sativa on scopolamine-induced spatial memory impairment in rats and its possible mechanism

Abstract: Hydro-alcoholic extract of NS prevents Sco-induced spatial memory deficits and decreases the AChE activity as well as oxidative stress of brain tissues in rats. Our results support the traditional belief about the beneficial effects of NS in nervous system. Moreover, further investigations are needed for better understanding of this protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 53 publications
5
55
1
Order By: Relevance
“…Administration of extract of NS (200 or 400 mg/kg, i.p.) for two weeks could avert scopolamine-induced memory deficit in rats, as the animals showed better execution in passive avoidance tests and diminished acetylcholinestrase (AChE) activity in the hippocampus and cortex tissue of the brain (Hosseini et al 2014). Nigella sativa extract was not able to improve memory function in ovariectomized rat.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of extract of NS (200 or 400 mg/kg, i.p.) for two weeks could avert scopolamine-induced memory deficit in rats, as the animals showed better execution in passive avoidance tests and diminished acetylcholinestrase (AChE) activity in the hippocampus and cortex tissue of the brain (Hosseini et al 2014). Nigella sativa extract was not able to improve memory function in ovariectomized rat.…”
Section: Resultsmentioning
confidence: 99%
“…NS had anticholinesterase properties. The hydroalcoholic extract of NS prevented scopolamine-induced spatial memory deficits and decreased the acetylcholinesterase activity as well as oxidative stress of brain tissues in rats 138 .…”
Section: Neuro-protective Effectsmentioning
confidence: 86%
“…[23][24] Usually the animal is observed in the EPM for 5 minutes and is allowed to explore the conditions, would indicate a stress situation due to height and lack of protection due to the absence of walls. [25][26][27][28][29] Several authors have shown the anxiolytic effects of plants in human and in animal models. [26,[29][30][31] Nevertheless we did not find studies in literature that showed the effects of DA seeds in the behavior of Wistar rats.…”
Section: Discussionmentioning
confidence: 99%